Pioglitazone Upregulates Angiotensin Converting Enzyme 2 Expression in Insulin-Sensitive Tissues in Rats with High-Fat Diet-Induced Nonalcoholic Steatohepatitis - Wei Zhang; Yi-Zhi Xu; Bo Liu; Rong Wu; Ying-Ying Yang; Xiao-Qiu Xiao; Xia Zhang (The Scientific World Journal)
Background and Aim. Thiazolidinediones (TZDs) can improve hepatic steatosis in nonalcoholic steatohepatitis (NASH). Angiotensin (Ang) II, the primary effector of renin-angiotensin system (RAS), plays vital roles in the development and progression of NASH. And some AngII-mediated effects can be regulated by TZDs. Angiotensin-converting enzyme (ACE) 2, a new component of RAS, can degrade Ang II to attenuate its subsequent physiological actions. We aimed to evaluate the effects of TZDs on ACE2 expression in insulin-sensitive tissues in NASH rats. Methods. Forty rats were divided into the normal control, high-fat diet (HFD), pioglitazone control, and HFD plus pioglitazone groups. After 24 weeks of treatment, we evaluated changes in liver histology and tissue-specific ACE2 expression. Results. ACE2 gene and protein expression was significantly greater in liver and adipose tissue in the HFD group compared with normal control group, while was significantly reduced in skeletal muscle. Pioglitazone significantly reduced the degree of hepatic steatosis compared with the HFD group. Pioglitazone significantly increased ACE2 protein expression in liver, adipose tissue, and skeletal muscle compared with the HFD group. Conclusions. Pioglitazone improves hepatic steatosis in the rats with HFD-induced NASH and upregulates ACE2 expression in insulin-sensitive tissues.